Protection against lethal HAdV-4 challenge in STAT1 mice by novel human monoclonal antibodies - Zhang, Xinyi; Zhu, Zhongge; Zhai, Peijie; Lv, Peng; Yang, You; Cheng, Chuanhang; Wang, Busen; Fang, Ting; Zhang, Guanying; Chi, Xiangyang; Li, Jianmin; Chen, Wei; et al. (Frontiers in Immunology, 2025)
IntroductionHuman adenovirus serotype 4 (HAdV-4) is an epidemic pathogen associated with severe acute respiratory disease (ARD) in both pediatric and adult populations. Currently, no available vaccine or therapeutic interventions specifically targeting adenoviruses are available.MethodsIn this study, we isolated peripheral blood mononuclear cells (PBMCs) from HAdV-4 infected donors and generated fully human monoclonal antibodies using single-cell PCR technology. The antibodies were first characterized for their neutralization efficacy both in vitro and in vivo. Subsequently, we predicted key functional residues through structural modeling of antigen-antibody complexes and validated their roles via mutagenesis studies. Finally, the mechanism of intracellular neutralization of antibodies was explored.ResultsThrough systematic screening, we successfully isolated seven antibodies with specific binding activity, among which monoclonal antibodies (mAbs) 2CF4 and 4AC3 exhibited potent neutralizing capacity against HAdV-4. Notably, we modeled adenoviral lethality using Stat1-/- transgenic mice, mAb 2CF4 conferred full protection against HAdV-4 infection in Stat1-/- transgenic mice. We identified critical amino acid residues, R99, R102 and T104 aa, of mAb 2CF4 by structural prediction of the antigen-antibody complex. Furthermore, the mAb 2CF4 neutralize the HAdV-4 through the interaction with the widely expressed cytoplasmic Fc-binding protein TRIM21.DiscussionOverall, mAb 2CF4 represents a promising candidate for safe and effective prophylactic and therapeutic strategies against HAdV-4 infection.